Influence of Hospital Outdoor Rest Space on the Eye Movement Measures and Self-Rating Restoration of Staff - Weiyi Cui; Zao Li; Xiaodong Xuan; Qingtao Li; Lei Shi; Xin Sun; Kai Zhu; Yi Shi (Frontiers Media S.A., 2022)
ObjectiveTo investigate the effect of hospital outdoor rest space on the eye movement measures and self-rating restoration of staff.BackgroundRelieving the pressure of hospital staff through exposure to hospital outdoor rest space is essential, but there is a scarcity of research on the impact of hospital outdoor rest space on the eye movement measures and self-rating restoration of staff, especially for large Chinese hospitals.MethodsCross-analysis was conducted based on the eye movement measures of 76 staff members obtained by eye movement tracking equipment in combination with the self-rating restoration scale and hospital outdoor rest space picture attributes (element proportion and position, brightness and saturation).ResultsThe differences in eye movement measures of different staff attributes (occupation, age, and gender) were identified, and the effects of hospital outdoor rest space picture attributes on the eye movement measures and self-rating restoration scale of staff were summarized. A number of proposals were also formulated: hospital outdoor rest space should be set up close to the working area of the group of medical staff; attention should be paid to the actual needs of senior staff members and the work pressure of junior nurses; the exposure to natural environment should be increased and the proportion of hard artificial elements should be reduced; the natural environment should be placed in the visual center; the saturation and brightness of hospital outdoor rest space should be increased; and staff members should have access to the sky environment in a variety of ways.ConclusionThe present study is an empirical study of evidence-based design on hospital outdoor rest space in China, and the results reveal the effects of hospital outdoor rest space on the eye movement measures and self-rating restoration of staff.